2022
DOI: 10.3389/fonc.2022.858202
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Newly Diagnosed Acute Myeloid Leukemia Patients Treated With Hypomethylating Agents With or Without Venetoclax: A Propensity Score-Adjusted Cohort Study

Abstract: There is a deficiency of real-world data on the impact of combining venetoclax (VEN) with hypomethylating agents (HMAs) in newly diagnosed acute myeloid leukemia (AML) patients. We conducted a single-center, propensity-adjusted retrospective cohort study to compare composite complete remission (CCR) rates, median overall survival (m-OS) and median event-free survival (m-EFS). A total of 170 adult AML patients were treated with first-line azacitidine (AZA) or decitabine (DEC) +/- VEN. Median age was 71 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…While we observed that some characteristics such as gender, age, and karyotype were reasonably similar in the considered real-world studies and in the RCT of DiNardo et al, we were not able to evaluate the prevalence of other important prognostic factors (e.g., ECOG performance status scale, baseline cytopenia grade, pre-treatment laboratory values, such as potassium, phosphate, uric acid, calcium, and creatinine) [43]. A possible heterogeneity of the clinical features among patients included in the different studies conducted in this setting was Matthews et al [27], Mustafa et al [38], and Winters et al [42] were considered in this analysis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…While we observed that some characteristics such as gender, age, and karyotype were reasonably similar in the considered real-world studies and in the RCT of DiNardo et al, we were not able to evaluate the prevalence of other important prognostic factors (e.g., ECOG performance status scale, baseline cytopenia grade, pre-treatment laboratory values, such as potassium, phosphate, uric acid, calcium, and creatinine) [43]. A possible heterogeneity of the clinical features among patients included in the different studies conducted in this setting was Matthews et al [27], Mustafa et al [38], and Winters et al [42] were considered in this analysis.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, although the trial of DiNardo et al reported a median overall survival of 14.7 months (95% CI 11.9-18.7), real-world studies showed substantially lower survival. With the only exception of Cherry et al and Mirgh et al, which reported a median survival of more than 15 months, the other authors showed an overall survival ranging between 4 and 13 months [21,24,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. As a consequence, the pooled median survival in our meta-analysis was 9.37 months (95% CI 8.81-10.5), significantly lower than that reported by DiNardo et al This difference was also confirmed in the secondary analyses that we performed, in particular after we excluded studies enrolling subjects with worse prognoses (i.e., secondary, therapy-related, and TP53mutated AML).…”
Section: Discussionmentioning
confidence: 97%
“…Retrospective analyses are conflicting, with no definitive differences in response rates between azacitidine‐venetoclax and decitabine‐venetoclax in the first‐line setting [ 16 ]. In one retrospective study, the median overall survival significantly favored the azacitidine‐venetoclax group at 12.3 months compared to 2.8 months with decitabine‐venetoclax [ 17 ]. In contrast, other retrospective analyses showed a non‐significant survival benefit favoring decitabine‐venetoclax over azacitidine‐venetoclax [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypomethylating agents, such as azacytidine and decitabine, have become a milestone in treatment of older AML and high-risk MDS patients with good efficacy and safety profile ( Serio B et al, 2022 ). In 2018, the Bcl-2 inhibitor venetoclax has been added to hypomethylating agents or low-dose cytarabine for treatment of newly diagnosed AML patients aged 75 or older not eligible for high-dose standard chemotherapy based on phase III clinical trial results ( DiNardo CD et al, 2020 ; Stein EM et al, 2020 ; Pollyea DA et al, 2021 ; Labrador J et al, 2022 ; Mustafa Ali MK et al, 2022 ; Wolach O et al, 2022 ). However, real-world data are still few.…”
Section: Discussionmentioning
confidence: 99%